Co-infecção HIV/HTLV-1 e 2: perfil soro-epidemiológico entre portadores do HIV/SIDA usuários de uma instituição de ensino superior - Amazônia, Brasil - MOTTA, André Luis Mendes da (2023)
This survey was carried out from October, 2006 to May, 2007 and the objective was to study the prevalence of the infection for HTLV in patient infection bearers for the virus of the human immunodeficiency, larger of 18 years, in João de Barros Barreto University Hospital, in the city of Belém, Pará, as well as analyzing possible risk factors associated to the co-infection and some partner-demographic aspects of the population in study. Participated in the study 36 patient that, after written consent, were submitted to the individual interview and collection of 5 ml of blood destined to the research of the infection markers by HTLV-1 and 2. To each participant a questionnaire was applied standardized for the obtaining of information on the characteristics socioeconomic, demographic and to the several risk factors investigated, regarding the exhibition parenteral, sexual and household contact. In the studied population the prevalence of the infection for HTLV-1 and 2 in the individuals positive HIV was of 2,8. As the demographic and socioeconomic characteristics, 66,7% (24) were male and 33.3% (12) were female, the overall prevalence of color was the brown with 72,1%, most of the interviewees was single (44,5%; 16/36), little more of the interviewees' half (55%; 20/36) had already accomplished blood transfusion, a considerable number of the interviewees (20%; 7/36) were already arrested, besides 28% (10/36) have already referred to have used drugs didn't inject and 11% (4;36) have already referred to have used drugs injected. The interviewees' largest portion was heterosexual (78%; 28/36). More of the patients interviewees' half (55%; 20/36) it never used preservatives in the sexual relationships before the infection for HIV. The patient of the population studied that she showed infected by HTLV have interesting characteristics that in a certain way are indicative of the increased risk of infection for this virus. Although it has been investigated in the population of HIV/sida carriers, the joined prevalence resembles it the observed ones in studies with the general population. Probably, the amostral size has been a factor to contribute for this result. Magnifying of the study is suggested better to define the prevalence of this co-infection, in these sick people.